Comparative analysis and design method of shear strength for hybrid SPR-SDS joints in thin-walled steel structures. (October 2021) - Xie, Zhiqiang; Zhang, Wenying; Chen, Tian; Zhou, Daxing; Shi, Leilei; Tang, Yi; Yu, Cheng
Abstract: This paper presents a new hybrid joint aimed at improving the defects of simple self-piercing rivet (SPR) or self-drilling screw (SDS) in thin-walled steel structures. This hybrid SPR-SDS joints took advantage of mechanical performance and construction technology for both simple SPR and SDS joints. A total of 132 hybrid joints were tested to evaluate structural behavior and capacity in shear. The differences among simple SPR joint, simple SDS joint and hybrid SPR-SDS joints were compared and analyzed. The parameters of sheet thickness, thickness ratio and fastener arrangement were considered with regard to their influences on shear behavior and failure mechanism. The results showed that hybrid joints could fully combine and exploit the advantages of SPR and SDS. The hybrid SPR-SDS joint could effectively improve the shear strength, stiffness and ductility of the simple SDS joint by 10.5%, 539.1.3% and 381.9%, respectively. The hybrid joint also demonstrated that the deformation and energy dissipation were 107.4% and 25% higher than the simple SPR joint, respectively. In addition, this paper proposes a new design method of shear strength for the hybrid joint. The design method was not only more accurate, but also could consider more comprehensive failure modes in design than the existing methods.